2015
DOI: 10.1002/aqc.2584
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating early life stages of fishes into estuarine spatial conservation planning

Abstract: 1. Many species of fish depend on estuaries to complete their development. Most of them have a planktonic early life stage, and adults of the same species often live in a different habitat.2. The aim was to assess the importance of incorporating data on fish eggs and larvae in systematic conservation planning at the Patos Lagoon estuary, Brazil.3. Different scenarios, where fish larvae and eggs were or were not included in the systematic conservation planning process, were investigated.4. An estimate of artisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 53 publications
0
9
0
3
Order By: Relevance
“…Este tipo de esfuerzo no solo incrementa la información general sobre una de las fases de desarrollo críticas para el componente íctico de una región, sino que también proporciona información relevante que puede ser utilizada en el marco de las acciones direccionadas a valorar y conservar la biodiversidad marina local (Warner et al, 2000). Además, uno de los insumos de conocimiento requeridos para comenzar a entender los patrones de distribución espacial, la variación temporal de la abundancia y las relaciones ecológicas con el hábitat disponible de los peces adultos, es conocer la identidad taxonómica de sus larvas y establecer como estas varían espacial y temporalmente (Hermes-Silva et al, 2009, Costa et al, 2015. Por lo tanto, los resultados obtenidos en la presente investigación son de particular importancia para fortalecer en el corto plazo las acciones de manejo de los recursos naturales asociados a la zona costera de la alta Guajira, incrementando simultáneamente el conocimiento sobre la diversidad biológica del recientemente declarado Parque Nacional Natural Portete-Kaurele.…”
Section: Discussionunclassified
“…Este tipo de esfuerzo no solo incrementa la información general sobre una de las fases de desarrollo críticas para el componente íctico de una región, sino que también proporciona información relevante que puede ser utilizada en el marco de las acciones direccionadas a valorar y conservar la biodiversidad marina local (Warner et al, 2000). Además, uno de los insumos de conocimiento requeridos para comenzar a entender los patrones de distribución espacial, la variación temporal de la abundancia y las relaciones ecológicas con el hábitat disponible de los peces adultos, es conocer la identidad taxonómica de sus larvas y establecer como estas varían espacial y temporalmente (Hermes-Silva et al, 2009, Costa et al, 2015. Por lo tanto, los resultados obtenidos en la presente investigación son de particular importancia para fortalecer en el corto plazo las acciones de manejo de los recursos naturales asociados a la zona costera de la alta Guajira, incrementando simultáneamente el conocimiento sobre la diversidad biológica del recientemente declarado Parque Nacional Natural Portete-Kaurele.…”
Section: Discussionunclassified
“…Various other topics are addressed in the studies analyzed, including the mapping of abiotic factors to provide subsidies for zoning (Pereira, 2016), and the proposal of a new approach to including climate change into the planning of protected areas through a gap analysis of marine protected areas (Magris et al, 2015). One study assesses issues in protected area management (Gerhardinger et al, 2011), while other studies include fisheries management (Costa et al, 2016;Prestrelo and Vianna, 2016) and fish biology (Costa et al, 2016).…”
Section: The Brazilian Contextmentioning
confidence: 99%
“…Thus, MSP is one element of ocean or sea use management, whereas zoning plans and other regulations are one of a set of management actions for implementing MSP (Ehler and Douvere, 2009). Whether zones are highly, moderately, or weakly regulated influences the overall protection level of MPAs (Costa et al, 2016;Horta e Costa et al, 2016). Therefore, zoning applies to the management of MPAs considering their zone classification and the International Union for the Conservation of Nature (IUCN) categories of protected areas (Dudley, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These vegetated areas are used as nurseries and habitats by important marine and estuarine fishing resources such as pink shrimp (Farfantepenaeus paulensis), blue crab (Callinectes sapidus), mullet (Mugil platensis), bluefish, catfish and whitemouth croaker (Micropogonias furnieri) (D'INCAO, 1991;GARCIA et al, 1996;VIEIRA, 1997;ASMUS, 1989;COSTA et al, 2015;RUAS et al, 2014), which sustain a local economy involving more than 6000 artisanal and 3000 industrial fishermen (REIS, 1992;HAIMOVICI et al, 1997;KALIKOSKI;VASCONCELOS, 2012). A recent study of fisheries management and conservation in Patos Lagoon concluded that the local vegetated shallow bottoms are essential fish habitats that should be preserved as no-take zones (COSTA et al, 2015). Fluvial discharge and winds are the driving forces behind the Patos Lagoon's hydrology, whereas the influence of the low tide (~ 0.4 m) is limited to the estuary mouth (MÖLLER et al, 2010).…”
Section: Patos Lagoon Estuary (Rio Grande Do Sul State)mentioning
confidence: 99%